Semantic priming and reading skills among Spanish-speaking dual language learners. Issue 5 (28th May 2022) - Goodrich, J. Marc; Leiva, Sergio
ABSTRACT: Substantial research among bilingual adults indicates that exposure to words primes other semantically related words within and across languages, as well as the direct translation equivalents [e.g. Chen and Ng 1989. "Semantic Facilitation and Translation Priming Effects in Chinese-English Bilinguals." Memory & Cognition 17: 454–462]. However, there is less research on semantic and translation priming among bilingual children. The purpose of this study was to evaluate semantic priming effects as an indicator of underlying lexical quality among Spanish-speaking dual language learners (DLLs) in the U.S., including examination of whether semantic and translation priming effects were related to children's reading-related skills. Ninety-five Spanish-speaking DLLs in second and fourth grade completed an eye-tracking semantic priming task along with measures of English and Spanish reading-related skills. Results indicated that there were consistent translation priming effects, with observed translation priming stronger from English to Spanish than from Spanish to English. Additionally, there were consistent within-English semantic priming effects. Results suggested that semantic priming effects were stronger for children with higher levels of English vocabulary and reading comprehension than they were for children with lower levels of English vocabulary and reading comprehension. Findings are discussed in the context of theoretical models of bilingual language processing, as well as the lexical quality hypothesis [e.g. Perfetti 2007. "Reading Ability: Lexical Quality to Comprehension." Scientific Studies of Reading 11: 357–383].